Persistence of Effects of VLBW/PT Birth Status and Maternal Emotional Availability (EA) on Child EA Trajectories - Stack, Dale M.; Matte-Gagné, Célia; Dickson, Daniel J. (Frontiers in Psychology, 2019)
Few studies have examined the longitudinal impact of birth status on the infant-mother relationship and on children’s socio-emotional development. In the present study we investigated developmental patterns of such relationships (using the Emotional Availability (EA) Scales) in fullterm and VLBW/PT infants from infancy to emerging school age. Our objectives were to: (a) model the developmental trajectories of EA dimensions (maternal sensitivity, structuring, nonhostility; child responsiveness, involvement) in a VLBW/PT and fullterm sample, (b) identify potential effects of VLBW/PT status on these trajectories, and (c) determine whether the effects of VLBW/PT status on children’s socio-emotional development (child EA) remained after accounting for the effect of maternal EA. Child-mother dyads (n=109) were observed in home-based interactions (face-to-face and free play) when children were 6, 12, 18 and 57-months-old in fullterm (37-41 weeks, >2500g; n=48) and healthy VLBW/PT (26-32 weeks gestation, birth weight 800-1500g, corrected for gestational age; n=61) children. Developmental trajectories of maternal and child EA were assessed using multilevel growth modeling in Mplus. Results indicated that, even after controlling for maternal EA, there was a persistent negative effect of VLBW/PT birth status on child EA trajectories. Both initially and over time, VLBW/PT infants lagged behind their fullterm counterparts on levels of responsiveness and involvement with mothers. There was also a persistent positive effect of maternal EA (sensitivity and structuring) on child EA trajectories. Higher average levels of maternal sensitivity and structuring across time were also associated with higher and persistent levels of child responsiveness and involvement of their mothers. Importantly, results held after modeling both effects together, and after controlling for maternal education and child gender. Our results have implications for VLBW/PT children’s development, the parent-child relationship, and integrating family level factors and relationship dimensions in early prevention and intervention programs.